2015
DOI: 10.1039/c5ra03190g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high methoxyl pectin and gellan including psyllium gel on Doogh stability

Abstract: The influence of three stabilizers, psyllium seed hydrocolloid (PSH, 0.25% w/w), high methoxyl pectin (HMP, 0.25% w/w), and gellan gum (GG, 0.05% w/w) alone or in a binary mixture, on the phase separation during 21 days of storage, mean particle size and distribution, x-potential, rheology, microstructure and sensory characteristics of an Iranian fermented milk drink "Doogh" was investigated. Results revealed that the stability of Dooghs prepared with binary combinations of HMP, PSH and GG was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
(128 reference statements)
2
14
0
Order By: Relevance
“…The results showed that all samples containing hydrocolloid were stable up to 7 days of storage but after a week, the physical stability of the doogh samples decreased because of overacidification, large particle sedimentation and casein aggregation at the bottom during the storage period (Hashemi et al . ). There was a significant difference between control samples and samples containing hydrocolloids.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed that all samples containing hydrocolloid were stable up to 7 days of storage but after a week, the physical stability of the doogh samples decreased because of overacidification, large particle sedimentation and casein aggregation at the bottom during the storage period (Hashemi et al . ). There was a significant difference between control samples and samples containing hydrocolloids.…”
Section: Resultsmentioning
confidence: 97%
“…; Azarikia and Abbasi ; Hashemi et al . ). Probably, the interactions between the chains were the cause of the increases in the apparent viscosity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Prolonging the shelf life of natural cheese and finding the additional ways to apply unsold natural cheese are the main reasons for developing processed cheese (Solowiej et al 2014). Use of emulsifying salts in the cheese structure has some functions in the development of a stable dairy emulsion (homogenous and not phase separated) until spray drying for cheese powder, or during cooling and storage for processed cheese, e.g., pH adjustment, binding of CaCl 2 , casein dispersion and fat emulsification (Lucey et al 2011;Hashemi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To describe the sensory properties, a sensory profiling method was applied. This procedure consisted of two phases, an initial phase to select, train and validate the assessors and a subsequent phase focusing on the evaluation of the samples [21]. Trained panelists were thus selected on the basis of perceived verbal skills, motivation, regular use of fish and fishery products and the ability to replicate their results.…”
Section: Sensory Attributesmentioning
confidence: 99%